Tax Compliance Behavior among Self-Employed Professionals: A Behavioral Economics Perspective - Anisa Ayu Dwi Lestari (Journal of Taxation Insights Policy Practice, 2025)
Tax compliance among self-employed professionals is a critical issue for policymakers. This study employs a mixed-methods research design, combining both quantitative and qualitative approaches to investigate the behavioral factors influencing tax compliance behavior. The study identifies the key drivers of non-compliance, including psychological biases, perceptions of fairness, and trust in tax authorities. Factor analysis confirms that perceived fairness and tax morale are the primary drivers of tax compliance. Social norm campaigns and behavioral nudges are cost-effective strategies to influence compliance behavior, reducing the need for costly enforcement measures. These findings contribute to the existing literature on tax compliance by integrating behavioral economics with traditional compliance models. This research demonstrates that enhancing trust and ensuring transparency in tax administration can significantly improve voluntary compliance, particularly in a demographic that often operates outside conventional tax structures.